“THE USE OF STYLISTIC DEVICES IN RUSSIAN AND ENGLISH PROVERBS” (Journal of Universal Science Research, 2025)
This article examines stylistic devices in proverbs, focusing on English and Russian paremiology. It analyses key figurative elements, including metaphor, alliteration, rhyme, and personification, to highlight their role in the meaning and memorability of proverbial speech. The study finds that stylistic devices are widely used in both languages, with slight differences in usage. By comparing some linguistic features, the research provides insight into how different cultures use stylistic devices in proverbs to encode wisdom and shared experiences.